Epidemiology of Thyroid Carcinomas in North Macedonia (1999-2015) - Makazlieva Tanja; Vaskova Olivija; Stojanoski Sinisha; Manevska Nevena; Miladinova Daniela; Velikj Stefanovska Vesna (SAGE Publishing, 2021)
Objective: We have set as objective to analyze epidemiological data of diagnosed thyroid carcinoma (TC) cases, incidence and prevalence rate by gender, age, histopathological type, and statistical regions in R. of N. Macedonia during the period 1999 to 2015. Material and Methods: Retrospective analysis of medical data collected from the 2 state thyroid departments. Inclusion criteria included newly diagnosed cases of TC in appropriate years for the period 1999 to 2015. We have evaluated: yearly incidence rate, incidence and prevalence by gender, age, the distribution in 8 statistical state regions and histopathological types and subtypes representation. Results: A total number of 422 TC patients were detected, average incidence rate of 1.22/10 5 , with most prevalent papillary TCs79.5%, followed by follicular 10.9%, medullar 4.1%, anaplastic 3.1%, and other rare types with 2.3%. The highest incidence rate was detected in Skopje region, while the lowest in Southeast and the Polog region. The total prevalence rate for the female gender was 32.61/10 4 and for male 9.27/10 4 (f/m ratio = 3.52:1), with lowest female/male difference found in the elderly > 65 years (f/m = 2.21/1). Conclusion: Compared with regional epidemiological data we can conclude that Republic of N. Macedonia has very low incidence and prevalence rate, while female/male ratio was similar to that described in the literature. Our low incidence and prevalence rate may be due to 2 possible reasons, 1 would be insufficient diagnosis of only small portion of the real cases in the population, or the second reason may be a real low incidence resulting of specific etiopathogenetic circumstances.